Interpersonal relations of pregnant women post-HIV diagnosis in Thembisile Hani, South Africa - Andile G. Mokoena-de Beer; Sister V. Mahlangu; Eugene M. Makhavhu (Southern African Journal of HIV Medicine)
Background: HIV is a major public health issue in South Africa, with around 7.7 million people living with the virus by 2023, including 4.9 million women. In 2022, 257 171 pregnant women received antiretroviral therapy to prevent mother-to-child transmission.